Metrology of additively manufactured lattice structures by X-ray tomography (Transactions on Additive Manufacturing Meets Medicine, 2020)
Additive manufacturing allows complexity of manufactured structures, allowing entirely new design capabilities. In the context of complex structure design, lattice structures hold the most promise for high complexity, tailorable and ultra-lightweight structures. In medical applications, these structures find application especially in bone implants – allowing matching of local elastic modulus of implant to that of bone and also allowing osseointegration. With this new complexity comes new manufacturing quality control and metrology challenges. Traditional metrology tools cannot access the entire structure and the only reliable method to inspect the inner details of these structures is by X-ray tomography. This work highlights the challenges of this process, demonstrating a workflow for dimensional metrology of coupon lattice samples. The confidence gained by inspection of such lattice coupons support the application of these lattices in end-use parts. The same principles are applied to larger samples and limitations are discussed using examples of implants.
Keywords: X-ray tomography; metrology